Sargent's Painting Materials: New Discoveries and Their Implications. Issue 1 (2nd January 2018) - Townsend, Joyce H.; Rayner, Georgina
Abstract : Several paintboxes and palettes used by John Singer Sargent, now in collections in both the USA and UK because he worked in both countries, have been studied technically. The results are compared to the artist's training and oil painting practice over his lifetime, elucidated in a recent study. Sargent's selection of materials and use of portable gear, modular easels and palettes for outdoor work are contextualized within the practice of coeval European artists. He used a wide range of high-quality paints consistently over his lifetime, which facilitated obtaining supplies in whichever continent and city he was working.